2010
DOI: 10.1080/10538712.2010.495045
|View full text |Cite
|
Sign up to set email alerts
|

Educator Sexual Abuse: Two Case Reports

Abstract: Sexual abuse by educators has become an increasingly noted type of sexual abuse, especially among adolescents, for two reasons. First, there is a potential for these cases to be silent and prolonged and second, when disclosed, the forensic implications usually include both criminal and/or civil sanctions. For forensic case evaluations, developmental traumatology, or the intersection of the traumatic event(s) at a particular age of the student, is often the evaluating framework. We report on two forensic cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This victimization causes students to suffer serious emotional, educational, developmental, and health effects (M. E. Afifi et al, 2007; Burgess, Welner, & Willis, 2010; Felitti et al, 1998; Winks, 1982). Specifically, it is thought that the trauma the child sexual abuse victims experience may hinder their academic achievement and have a significant negative impact on their lives post-abuse (T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This victimization causes students to suffer serious emotional, educational, developmental, and health effects (M. E. Afifi et al, 2007; Burgess, Welner, & Willis, 2010; Felitti et al, 1998; Winks, 1982). Specifically, it is thought that the trauma the child sexual abuse victims experience may hinder their academic achievement and have a significant negative impact on their lives post-abuse (T.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it is thought that the trauma the child sexual abuse victims experience may hinder their academic achievement and have a significant negative impact on their lives post-abuse (T. O. Afifi, Brownridge, Cox, & Sareen, 2006; Burgess et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Harris Interactive (2001) for the American Association of University Women (AAUW) utilized a nationally representative sample of over 2000 students in Grades 8 through 11. They found that 38% of the students they surveyed reported that they were harassed by teachers or other school employees, with harassment including sexual comments, jokes, gestures, or looks; sexual rumors; sharing of sexual pictures, illustrations, or messages; and comments about sexual orientation (Burgess et al, 2010). In her 2004 report to the Department of Education, Shakeshaft found that prevalence rates of educator misconduct varied widely ranging anywhere from 3.75 to 50.3%.…”
Section: Prevalencementioning
confidence: 99%
“…Furthermore, abusive teachers use some tactics instead of physical force/violence in SA incidents towards students (Moulden et al, 2010;Shakeshaft, 2018). Although the rate of threat and violence is low, SA behaviors of teachers may cause psychological problems in both male and female students, such as delayed post-traumatic stress disorder (PTSD), depression and alcohol addiction (Burgess, Welner and Willis, 2010) just like in incest incidents (Finkelhor & Hashimma, 2001; as cited in Mototsune, 2015). As for the tactics they employ, some of these tactics include targeting children that are disadvantaged due to familial and psycho-social reasons, obtaining private knowledge about the victims, showing special attention to the victims they are targeting, supporting and rewarding them etc.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, SA incidents taking place in school and committed by teachers must be addressed from an educational point of view considering that children spend most of their times at schools after their families, SA may cause many psychological and social problems related to school (e.g., school phobia, school leaving) (Blakemore, Herbert, Arney, & Parkinson, 2017;Burgess et al, 2010;Celik et al, 2012;Kocturk & Bilge, 2018) and school counseling services are important for detecting and preventing SA. As there is a limited number of studies in the literature, characteristics of SA taking place in the school environment, as well as victims and abusive teachers are not known for sure, it is not possible to reach out to victims for study for ethical and other reasons, SA incidents at schools can be learned from the news (Celik et al, 2012) and the Turkish society uses the Internet and television most as a source of learning the news (Olkun, 2017), this study aims to examine news about SA taking place in the school environment published at news websites and to determine the nature of SA incidents, as well as individual characteristics of perpetrators and victims.…”
Section: Introductionmentioning
confidence: 99%